HLA-DR-DQ haplotypes and genotypes in Finnish patients with rheumatoid arthritis. Issue 11 (12th October 2004) - Laivoranta-Nyman, S; Möttönen, T; Hermann, R; Tuokko, J; Luukkainen, R; Hakala, M; Hannonen, P; Korpela, M; Yli-Kerttula, U; Toivanen, A; Ilonen, J
Abstract : Objectives: To elucidate the contribution of HLA-DR-DQ haplotypes and their genotypic combinations to susceptibility to rheumatoid arthritis, and to evaluate the various models for HLA associated risk for the disease in a series of Finnish patients. Methods: 322 Finnish patients with rheumatoid arthritis were typed for common north European HLA-DR-DQ haplotypes and compared with a series of 1244 artificial family based control haplotypes. Results: The association of the so called shared epitope (SE) haplotypes (DRB1*0401, *0404, *0408, and *01) with rheumatoid arthritis was confirmed. The DRB1*0401 haplotypes carried a far stronger risk for the disease than the (DRB1*01/10)-(DQA1*01)-DQB1*0501 haplotypes. Seven protective HLA haplotypes—(DRB1*15)-(DQA1*01)-DQB1*0602; (DRB1*08)-(DQA1*04)-DQB1*04; (DRB1*11/12)-DQA1*05-DQB1*0301; (DRB1*1301)-(DQA1*01)-DQB1*0603; (DRB1*1302)-(DQA1*01)-DQB1*0604; (DRB1*07)-DQA1*0201-DQB1*0303; and (DRB1*16)- (DQA1*01)-DQB1*0502—were identified. In accordance with the reshaped shared epitope hypothesis, all the protective DRB1 alleles in these haplotypes share either isoleucine at position 67 or aspartic acid at position 70 in their third hypervariable region motif. However, differences in the disease risk of haplotypes carrying the same DR but different DQ alleles were also found: (DRB1*07)-DQA1*0201-DQB1*0303 was protective, while (DRB1*07)-DQA1*0201-DQB1*02 was neutral. The same haplotypes carried different risks for rheumatoid arthritis depending on their combination in genotypes. Conclusions: When assessing the influence of HLA genes on the susceptibility to rheumatoid arthritis, not only should the HLA-DR or -DQ alleles or haplotypes be unravelled but also the genotype. The effect of HLA class II region genes is more complicated than any of the existing hypotheses can explain.